Autologous stem cell transplantation in multiple myeloma patients: utilization patterns and hospital effects. Issue 10 (23rd August 2020) - Jansen, Lina; Merz, Maximilian; Engelhardt, Monika; Weisel, Katja; Scheid, Christof; Straka, Christian; Langer, Christian; Salwender, Hans; Einsele, Hermann; Kröger, Nikolaus; Beelen, Dietrich W.; Dreger, Peter; et al.
Abstract: Evidence on volume outcome associations for autologous stem cell transplantation (ASCT) in multiple myeloma (MM) is limited. We investigated ASCT utilization patterns and volume outcome associations in the German National Registry for Stem Cell Transplants (DRST). MM patients with an upfront ASCT between 1998 and 2014 registered in the DRST were included. ASCT utilization increased strongly from 6% to 17% between 1999 and 2013 with the largest increase for patients aged 60–64 years (8–34%). The mean number of ASCTs conducted in the hospitals per year varied (quintiles, Q1:0.0–8.2 to Q5:31.0–102.7). Center volume was not associated with survival after upfront ASCT (lowest vs. highest center volume, hazard ratios and 95% confidence intervals: 0.95 (0.76–1.18), p = 0.92). Our findings may reflect a high standard of care and degree of specialization of centers performing ASCT for MM in Germany.